Factors Affecting Job Satisfaction of Non-Educational Personnel: A Study at Mahaputra Muhammad Yamin University - Nurhayati Nurhayati; Ida Nirwana; Yogi Pratama (Review of Ethics in Sustainable Finance and Accounting, 2025)
This study aims to analyse the effect of workload, compensation, and organisational communication on job satisfaction of non-educational staff at Mahaputra Muhammad Yamin University Solok. This research uses quantitative methodology with a sample of 39 respondents. Information was collected through questionnaires. Multiple regression analysis resulted in a regression equation Y = 8.510 + 0.486X1 + 0.219X2 + 0.126X3 + e. The calculated t value of 3.074 > t table 2.03011 and sig 0.004 < 0.05 indicates that workload (X1) significantly affects job satisfaction. Based on the results of the t test, compensation does not significantly affect job satisfaction (X2), as indicated by the t value of 1.731 < t table 2.03011 and sig value of 0.092 > 0.05. In addition, the calculated t value of 0.838 < t table 2.03011 and sig 0.408 > 0.05 indicate that job satisfaction and organisational communication (X3) are not significantly correlated. At Mahaputra Muhammad Yamin University in Solok, job satisfaction of non-educational personnel is influenced by workload, salary, and organisational communication, as indicated by the calculated F value of 28.339 > F table 3.27. The three variables have an influence of 70.8% on job satisfaction, based on the R Square value of 0.708 or 70.8%, while the variables not included in this study are 29.2%.